Pengaruh Disiplin kerja dan kompetensi Terhadap Kinerja perangakat Desa Talang Tangsi Kabupaten Lahat - Titi Hasanah; Markus Markus; Saparudin Saparudin (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the influence of work discipline and competence on the performance of Talang Tangsi Village officials, Lahat Regency. The method used in this research is a quantitative survey, where data is collected through questionnaires distributed to 52 randomly selected village officials. Data analysis was carried out using multiple linear regression to identify the extent to which work discipline and competence influence performance. The research results show that work discipline has a positive and significant influence on the performance of village officials, with a regression coefficient value of 0.45. This indicates that increasing work discipline will improve the performance of village officials. Competence also shows a significant positive influence on performance, with a regression coefficient value of 0.38. These findings underline the importance of competency development as a key factor in increasing the effectiveness of village officials' performance. Overall, this research concludes that both work discipline and competency play an important role in determining the performance of Talang Tangsi Village officials. In conclusion, based on the research results, it can be concluded that work discipline and competence have a significant effect together on the performance of Tangsi Village officials, Lahat Regency. Keywords: Competency, Lahat Regency, Performance, Village Apparatus, Work Discipline